Alunos com autismo na escola:um estudo de práticas de escolarização - Alves, Marcia Doralina (Universidade do Vale do Rio dos Sinos, 2015)
This study presents the results of an investigation into the education of students with autism, given the possible conditions under which such schooling took shape and was articulated as an imperative public post- inclusion policies. Born first from a study of the narratives produced by clinical discourses on these subjects in an attempt to point to an understanding of this medical knowledge that has been consolidating over the history of civilization. Also held a historic shift on the origins of the school , allowing to understand how individuals with autism was constituted initially from social apparatuses for their isolation in the late nineteenth century (nursing homes, psychiatric hospitals) to their inclusion in regular schools in the XXI century. Based on this universalization scenario of education is to present some problems about the effecting the education of students with autism in regular school. To this end, I seek to investigate this process in order to understand how the pedagogical practices directed at these students are established as true regimes. So, we decided to analyze interviews with professionals in the regular classroom and specialized educational services (ESA), both teachers of students with autism. In order to enhance the study, we sought an intersection of these interviews with pedagogical advice given by these teachers. Also added to the study, findings from three researches produced in Brazilian graduate programs in the period 2008-2011, dealing with the education of students with autism. As theoretical lenses developed from a careful study of the propositions of Michel Foucault on what was possible to appropriate, conducting a dialogue with Education. The survey found that the socialization of students with autism is the main dimension crafted by teachers and the fact that these students "do not perform activities like other students" causes the teacher to seek, in most cases , a diagnosis that reiterates this positioning , signaling for a student with poor conditions for learning the course content . We will see that the school is the result of a historical construction that was born in Modernity and despite an inclusive discourse, presents the contemporary with gaps to work with students with autism, establishing itself as a space that excludes those considered abnormal.
Keywords: Escolarização; Práticas pedagógicas; Alunos com autismo; Schooling; Pedagogical practices; Students with autism; ACCNPQ::Ciências Humanas::Educação